Chitosan-based adsorbents for remediation of toxic dyes from wastewater: A review on adsorption mechanism, reusability, machine learning based modeling and future perspectives - Nath, Jyotishka; Dewan, Mitali; Ghosh, Adrija; Ray, Suprakas Sinha; Orasugh, Jonathan Tersur; Lahiri, Basudev; Chattopadhyay, Dipankar; Adhikari, Arpita (International journal of biological macromolecules, 2025)
The disposal of recalcitrant dyes in aquatic environments from various industrial sectors is a threat to both the plant and animal kingdom. The presence of dyes in various water bodies undermines the availability of uncontaminated drinking water and may result in serious health-related issues and diseases. Therefore, it is of utmost importance to get rid of these harmful dyes from the aquatic environment. Hence various treatment techniques came to the fore, but they have their corresponding advantages and disadvantages. Several researchers have reported the adsorption of dyes with carbon-based composites, polymeric materials, and metal-based nanoparticles. However, the one with biocompatible materials or biopolymers deserves special attention as they are benign from an environmental viewpoint. We have chosen chitosan as our material of interest and elaborated on the positive aspects of chitosan as an excellent candidate for dye adsorption. Although a plethora of review articles has been disseminated in the past to underscore the utilization of chitosan-based adsorbents in the extraction of dyes, this manuscript endeavors to furnish a thorough examination of the complete adsorption process, encompassing its parameters and kinetics, thus facilitating a reader lacking foundational knowledge in this field to attain a more comprehensible understanding of the subject matter. This review also integrates a comprehensive overview of optimization methodologies for dye adsorption and examines relevant patents—an area that, to the best of our knowledge, has not been thoroughly addressed in previous review articles. Conclusively, it can be stated that chitosan can efficiently adsorb dye from wastewater showing good performance even after five cycles of adsorption/desorption. Moreover, several software programs can be used for optimizing maximum dye adsorption capacity of chitosan which shows well alignment with experimental results, thus making it suitable for real-life applications. [Display omitted] •Chitosan-based adsorbents show promising role in dye adsorption.•Chitosan-based adsorbents exhibit superior adsorption capacity due to various surface functional groups•Chitosan-based adsorbent materials are biocompatible, biodegradable, and cost-effective for dye adsorption